(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this work was to study K efficiency ofdifferent crops and determine the plant parameters affecting it. The studywas carried out using 14 different crops and cultivars grown on a sandysoil rich in humus, with two potassium fertilisation levels undercontrolled conditions. The studied crops showed different K efficiencyreflected in different dry matter yield production in unfertilised relative tofertilised treatments. All crops had, at low K supply, less than optimum Kconcentration in dry matter, indicating that the soil K concentration didnot meet the K requirement of the plants. Thus, the ability to produce highdry matter yield indicated superior adaptability to K deficiency. Theefficiency mechanisms employed by the different crops were low shootgrowth rate and/or high root length - shoot weight ratio and a high uptakerate per unit root, i.e. the influx, or low internal K requirement. Cropswith high influx had higher calculated concentration gradients, since theycaused further decrease of the concentration at the root surface. As such,they were able to create steeper concentration gradients between bulk soilsolution and root surface. This resulted in higher diffusive flux to theroots.